Capacity and site readiness for hypertension control program implementation in the Federal Capital Territory of Nigeria: a cross-sectional study - Ikechukwu A. Orji; Abigail S. Baldridge; Kasarachi Omitiran; Mainzhao Guo; Whenayon Simeon Ajisegiri; Tunde M. Ojo; Gabriel Shedul; Namratha R. Kandula; Lisa R. Hirschhorn; Mark D. Huffman; Dike B. Ojji (BMC, 2021)
Abstract Background Nigeria faces an increase in the burden of non-communicable diseases (NCDs), including cardiovascular diseases (CVDs), leading to an estimated 29% of all deaths in the country. Nigeria has an estimated hypertension prevalence ranging from 25 to 40% of her adult population. Despite this high burden, awareness (14-30%), treatment (< 20%), and control (9%) rates of hypertension are low in Nigeria. Against this backdrop, we sought to perform capacity and readiness assessments of public Primary Healthcare Centers (PHCs) to inform Nigeria's system-level hypertension control program's implementation and adaptation strategies. Methods The study employed a multi-stage sampling to select 60 from the 243 PHCs in the Federal Capital Territory (FCT) of Nigeria. The World Health Organization (WHO) Service Availability and Readiness Assessment was adapted to focus on hypertension diagnosis and treatment and was administered to PHC staff from May 2019 - October 2019. Indicator scores for general and cardiovascular service readiness were calculated based on the proportion of sites with available amenities, equipment, diagnostic tests, and medications. Results Median (interquartile range [IQR]) number of full-time staff was 5 (3-8), and were predominantly community health extension workers (median = 3 [IQR 2-5]). Few sites (n = 8; 15%) received cardiovascular disease diagnosis and management training within the previous 2 years, though most had sufficient capacity for screening (n = 58; 97%), diagnosis (n = 56; 93%), and confirmation (n = 50; 83%) of hypertension. Few PHCs had guidelines (n = 7; 13%), treatment algorithms (n = 3; 5%), or information materials (n = 1; 2%) for hypertension. Most sites (n = 55; 92%) had one or more functional blood pressure apparatus. All sites relied on paper records, and few had a functional computer (n = 10; 17%) or access to internet (n = 5; 8%). Despite inclusion on Nigeria's essential medicines list, 35 (59%) PHCs had zero 30-day treatment regimens of any blood pressure-lowering medications in stock. Conclusions This first systematic assessment of capacity and readiness for a system-level hypertension control program within the FCT of Nigeria demonstrated implementation feasibility based on the workforce, equipment, and paper-based information systems, but a critical need for essential medicine supply strengthening, health-worker training, and protocols for hypertension treatment and control in Nigeria.